Analysis of the sternum for sternal closure with bioabsorbable sternal pins. (June 2013) - Kawamura, Masashi; Masai, Takafumi; Matsue, Hajime; Yoshikawa, Yasushi; Sawa, Yoshiki
Purpose: Poly-L-lactide sternal pins have been reported to be beneficial for sternal closure. However, we sometimes experience a small sternum, and the size characteristics of the sternum have not been fully investigated. We analyzed size features of the sternum to determine the optimal size of sternal pin for sternal closure. Methods: Chest computed tomography scans were preoperatively obtained in 144 patients undergoing major cardiovascular surgery. We reviewed all scans at the level of the sternum, and measured the width of the bone marrow of the sternum on each computed tomography slice. Results: The mean values of bone marrow width of the sternal manubrium and body of male patients were significantly higher than those of females (manubrium: 38.6 ± 3.9 mm in males, 34.5 ± 3.3 mm in females, p  < 0.0001; body: 23.4 ± 3.7 mm in males, 20.8 ± 2.8 mm in females, p  < 0.0001). There was no correlation between the bone marrow width of the sternal body and body surface area in either males or females (males: r  = 0.08, p  = 0.45, females: r  = 0.08, p  = 0.58). Conclusion: To select the appropriate size of sternal pin, preoperative measurement of the bone marrow width of the sternum is recommended because it cannot be predicted from body size.